Optimalisasi Tiktok sebagai Media Dakwah di Era Digital dalam Meningkatkan Kualitas Pemahaman Agama pada Mahasiswa - Ramadona, Khoiro; Depi Putri; Erwin Rochmansyah; Elce Purwandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effectiveness of dakwah delivered through TikTok as a digital medium in shaping university students’ religious understanding, as well as to identify the strengths, limitations, and challenges associated with such digital dakwah. The research employed a descriptive qualitative approach, with data collected through in-depth interviews with eight informants. The findings indicate that TikTok has become a strategic platform for disseminating dakwah messages rapidly through visually engaging content, thereby attracting students who are highly active on social media. However, the platform’s short video duration may result in incomplete delivery of religious material and can lead to misconceptions if not supported by formal religious education and guidance from qualified scholars. The study also reveals that digital dakwah primarily functions as an introduction and an initial source of motivation, whereas deeper religious comprehension still requires conventional learning forums. In conclusion, dakwah via TikTok plays an important role in contemporary religious communication, but it must be supported by digital media literacy among both content creators and audiences to maintain the quality of religious understanding. Formal education should actively complement and integrate digital dakwah to achieve optimal impact. Keywords: Digital Dakwah, TikTok Preaching, Religious Communication